TCR Signaling: Mechanisms of Initiation and Propagation. Issue 2 (February 2018) - Courtney, Adam H.; Lo, Wan-Lin; Weiss, Arthur
Abstract : The mechanisms by which a T cell detects antigen using its T cell antigen receptor (TCR) are crucial to our understanding of immunity and the harnessing of T cells therapeutically. A hallmark of the T cell response is the ability of T cells to quantitatively respond to antigenic ligands derived from pathogens while remaining inert to similar ligands derived from host tissues. Recent studies have revealed exciting properties of the TCR and the behaviors of its signaling effectors that are used to detect and discriminate between antigens. Here we highlight these recent findings, focusing on the proximal TCR signaling molecules Zap70, Lck, and LAT, to provide mechanistic models and insights into the exquisite sensitivity and specificity of the TCR. Highlights: The interface of a T cell and an APC is thought to exert force on the TCR and increasing evidence indicates the TCR is mechanosensitive. During antigen detection, mechanical force may be important for antigen discrimination. Lck is basally active and phosphorylates the TCR complex and Zap70 on pMHC binding. Active Lck abundance and its coupling to the TCR during antigen encounter are able to influence affinity discrimination. A hallmark of TCR signaling is its sensitivity and specificity. How the strict TCR signaling hierarchy is enforced is continuing to emerge through structural insight into the substrate selectivity of Lck and Zap70 and how the activation of Zap70 is controlled. The emerging properties of the LAT signalosome include its assembly into liquid-like phase-separated clusters that contain phospho-LAT and its binding partners, which can enhance actin polymerization. These emerging properties reveal how LAT can function as foci of TCR signaling.